2022
DOI: 10.1038/s41598-022-12117-4
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil gelatinase-associated lipocalin as a prognostic biomarker of severe acute respiratory distress syndrome

Abstract: Neutrophil gelatinase-associated lipocalin (NGAL) is produced in the bronchial and alveolar cells of inflamed lungs and is regarded as a potential prognostic biomarker in various respiratory diseases. However, there are no studies on patients with acute respiratory distress syndrome (ARDS). NGAL levels in serum and bronchoalveolar lavage (BAL) were measured at baseline and on day 7 in 110 patients with ARDS. Baseline NGAL levels were significantly higher in ARDS patients than in healthy controls (serum 25 [14.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Additionally, LCN2 has been shown to induce antioxidants in vitro [ 17 ]. Elevated LCN2 expression has been observed in patients with chronic obstructive pulmonary disease and acute respiratory distress syndrome, which have been associated with increased oxidative stress levels [ 18 20 ]. Moreover, Ikezoe et al reported that patients with IPF had higher LCN2 levels in bronchoalveolar lavage fluid (BALF) than those with other interstitial pneumonia [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, LCN2 has been shown to induce antioxidants in vitro [ 17 ]. Elevated LCN2 expression has been observed in patients with chronic obstructive pulmonary disease and acute respiratory distress syndrome, which have been associated with increased oxidative stress levels [ 18 20 ]. Moreover, Ikezoe et al reported that patients with IPF had higher LCN2 levels in bronchoalveolar lavage fluid (BALF) than those with other interstitial pneumonia [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering that lung injury can occur during COVID-19, it is significant that lung epithelial damage is associated with elevated serum NGAL (sNGAL) levels. It was demonstrated that increased sNGAL can be a biomarker of pulmonary injuries in mechanically ventilated patients and can be associated with early mortality in patients with ARDS [13,14]. Physiologically, NGAL is present in the bloodstream at very low levels, which can increase significantly in the event of ischemic or toxic injury.…”
Section: Introductionmentioning
confidence: 99%
“…ALI is a common clinical syndrome that often results in acute respiratory failure [17], typically characterized by severe pulmonary edema and uncontrolled inflammation of the lungs [18]. The inflammatory response and pulmonary edema can rapidly deteriorate lung function, which may ultimately result in respiratory failure and multiple organ dysfunction syndrome [19,20]. Inflammation and oxidative stress are the primary triggers of ALI development [21].…”
Section: Introductionmentioning
confidence: 99%